2014
DOI: 10.1371/journal.pone.0090314
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Smoking on Levels of Endothelial Progenitor Cells and Microparticles in the Blood of Healthy Volunteers

Abstract: BackgroundCigarette smoking, both active and passive, is one of the leading causes of morbidity and mortality in cardiovascular disease. To assess the impact of brief smoking on the vasculature, we determined levels of circulating endothelial progenitor cells (EPCs) and circulating microparticles (MPs) following the smoking of one cigarette by young, healthy intermittent smokers.Materials and Methods12 healthy volunteers were randomized to either smoking or not smoking in a crossover fashion. Blood sampling wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 41 publications
5
55
1
2
Order By: Relevance
“…The same CSE-EV were less potent inducers of monocyte adhesion to endothelial cells than EV secreted by unexposed cells , questioning a role of CSE-induced EV in immune cell recruitment. Several human and animal studies that assessed in vivo effects of respiratory exposures were not able to link changes in circulating EV to alterations in inflammatory markers (Emmerechts et al 2012a(Emmerechts et al , 2012bLevanen et al 2013;Mobarrez et al 2014). Several investigators even found that smokers displayed decreased concentrations of circulating PS + EV compared to nonsmokers (Badrnya, Baumgartner, and Assinger 2014;Enjeti et al 2017;Grant et al 2011).…”
Section: Conflicting Datamentioning
confidence: 99%
See 4 more Smart Citations
“…The same CSE-EV were less potent inducers of monocyte adhesion to endothelial cells than EV secreted by unexposed cells , questioning a role of CSE-induced EV in immune cell recruitment. Several human and animal studies that assessed in vivo effects of respiratory exposures were not able to link changes in circulating EV to alterations in inflammatory markers (Emmerechts et al 2012a(Emmerechts et al , 2012bLevanen et al 2013;Mobarrez et al 2014). Several investigators even found that smokers displayed decreased concentrations of circulating PS + EV compared to nonsmokers (Badrnya, Baumgartner, and Assinger 2014;Enjeti et al 2017;Grant et al 2011).…”
Section: Conflicting Datamentioning
confidence: 99%
“…Several investigators even found that smokers displayed decreased concentrations of circulating PS + EV compared to nonsmokers (Badrnya, Baumgartner, and Assinger 2014;Enjeti et al 2017;Grant et al 2011). In part, the failure to detect proinflammatory changes in EV in response to respiratory toxicants in vivo may be due to (1) use of relatively mild and acute exposures (Levanen et al 2013;Mobarrez et al 2014) or (2) the fact that current methods are not sensitive enough to detect subtle changes in EV and inflammatory mediators in study populations without clinical disease.…”
Section: Conflicting Datamentioning
confidence: 99%
See 3 more Smart Citations